The impact of patient characteristics and lifestyle factors on the risk of an ipsilateral event after a primary DCIS: A systematic review. (April 2020) - Alaeikhanehshir, Sena; Engelhardt, Ellen G.; van Duijnhoven, Frederieke H.; van Seijen, Maartje; Bhairosing, Patrick A.; Pinto, Donna; Collyar, Deborah; Sawyer, Elinor; Hwang, Shelley E.; Thompson, Alastair M.; Wesseling, Jelle; Lips, Esther H.; et al.
Abstract: Objective: The majority of 'low-risk' (grade I/II) Ductal Carcinoma In Situ (DCIS) may not progress to invasive breast cancer during a women's lifetime. Therefore, the safety of active surveillance versus standard surgical treatment for DCIS is prospectively being evaluated in clinical trials. If proven safe and selectively implemented in clinical practice, a significant group of women with low-risk DCIS may forego surgery and radiotherapy in the future. Identification of modifiable and non-modifiable risk factors associated with prognosis after a primary DCIS would also enhance our care of women with low-risk DCIS. Methods: To identify modifiable and non-modifiable risk factors for subsequent breast events after DCIS, we performed a systematic literature search in PUBMED, EMBASE and Scopus. Results: Six out of the 3870 articles retrieved were included for final data extraction. These six studies included a total of 4950 patients with primary DCIS and 640 recorded subsequent breast events. There was moderate evidence for an association of a family history of breast cancer, premenopausal status, high BMI, and high breast density with a subsequent breast cancer or further DCIS. Conclusion: There is a limited number of recent studies published on the impact of modifiable and non-modifiable risk factors on subsequent events after DCIS. The available evidence is insufficient to identify potential targets for risk reduction strategies, reflecting the relatively small numbers and the lack of long-term follow-up in DCIS, a low-event condition. Highlights: Need for risk management strategies for untreated DCIS patients. Limited evidence for association between lifestyle factors and prognosis after DCIS. Positive family history, premenopausal status, high breast density associated with prognosis.